Predicting and evaluating seasonal water turbidity in Lake Balkhash, Kazakhstan, using remote sensing and GIS - Mishra, Kanchan; Choudhary, Bharat; Fitzsimmons, Kathryn E. (Frontiers in Environmental Science, 2024)
Lake Balkhash is Asia’s third-largest lake and an endorheic basin. The lake and its contributing tributaries provide essential water and ecosystem services to the surrounding population, particularly in the Kazakh region. With approximately 2.5 million people living in the areas such as Almaty oblast, Zhetisu oblast, several districts of Karagandy oblast, and Abay province, monitoring and maintaining the lake’s health and water quality is essential for the sustainable management of water resources. The hydrology of Lake Balkhash has been significantly impacted in recent decades by a warming climate, landuse landcover changes, and water-consuming economic activities, the latter of which are driven by population growth and expansion. Turbidity – the measurement of water clarity - serves as a major indicator of water health. Here, we analyze spatial and temporal variability in turbidity across Lake Balkhash by mapping the normalized difference turbidity index (NDTI) based on Landsat data for 1991-2022. We consider major exploratory variables such as precipitation, near-surface temperature, wind speed and direction, water level, and landuse landcover (LULC) within the catchment. We find an overall decrease in turbidity over interannual and seasonal timescales. We observe significant negative correlations between NDTI, near-surface temperature, and water level at both scales but no clear relationship between turbidity and precipitation or wind variables. Among the LULC variables, grassland and bareland near Lake Balkhash showed a positive correlation with NDTI but have spatially decreased over time. Conversely, shrubland and wetland exhibit a negative correlation with NDTI; however, this has spatially increased with time. Our results highlight the significant impact of rising temperatures, anthropogenically influenced water levels, and the LULC variables on turbidity. The turbidity dynamics, in turn, influence the circulation, oxidation, and overall health of Lake Balkhash's water. Therefore, the study emphasizes that the warming climate and alterations in the lake's hydrology have a considerable impact on water quality. This suggests that monitoring water health alone may not suffice to mitigate the impacts of climate change and human activities. However, a more comprehensive approach is needed to sustainably manage and conserve dryland water resources.